Propagation of premixed flames in the presence of Darrieus–Landau and thermal diffusive instabilities - Creta, Francesco; Lapenna, Pasquale Eduardo; Lamioni, Rachele; Fogla, Navin; Matalon, Moshe (Combustion and flame, 2020)
We study the propagation of premixed flames, in the absence of external turbulence, under the effect of both hydrodynamic (Darrieus–Landau) and thermodiffusive instabilities. The Sivashinsky equation in a suitable parameter space is initially utilized to parametrically investigate the flame propagation speed under the potential action of both kinds of instability. An adequate variable transformation shows that the propagation speed can collapse on a universal scaling law as a function of a parameter related to the number of unstable wavelengths within the domain nc. To assess whether this picture can persist in realistic flames, a DNS database of large scale, two-dimensional flames is presented, embracing a range of nc values and subject to either purely hydrodynamic instability (DL) or both kinds of instability (TD). With the aid of similar DNS databases from the literature we observe that when adequately rescaled, propagation speeds follow two distinct scaling laws, depending on the presence of thermodiffusive instability or lack thereof. We verify the presence of secondary cutoff values for nc identifying (a) the insurgence of secondary wrinkling in purely hydrodynamically unstable flames and (b) the attainment of domain independence in thermodiffusively unstable flames. A possible flame surface density based model for the subgrid wrinkling is also proposed.